Contribution of Dentist Anesthesiologists to Dental Anesthesiology Research - Ganzberg, Steven (The American Dental Society of Anesthesiology, 2011)
In order to determine if dentist anesthesiologists (DAs) actively contribute to research in the field of anesthesiology, and thus contribute new knowledge to the field, an extensive literature search was accomplished. DAs make up only 1.5% of dentists who actively contribute to anesthesia research but account for 10% of publications. To determine if the impact of DA research was similar to the American Dental Association (ADA) recognized specialties, h-indices of noted researchers in other specialties were compared to the h-indices of noted DA researchers. The results show that the impact of top DA researchers in dental anesthesiology is similar to the impact of top dental specialty researchers, despite lack of academic departments in dental schools where a large percentage of dental research is completed. Dentist anesthesiologists actively contribute to the research in anesthesiology for dentistry and thus, actively contribute to new knowledge in the field.